Hubungan Pengetahuan dan Peran Orang Tua dengan Perawatan saat Menstruasi pada Remaja Putri di SLTP Negeri 6 Kota Jambi Tahun 2007 - Sri Yun Utama (Universitas Batanghari Jambi, 2009)
Female teenagers are expected to be able to take good care of themselves. Expecially when they are having their period (menstruation). Otherwise, they while easily get viruses or bacteria. This is descriptive research with cross-sectional approach. It’s purpose is to describe the correlation of knowledge, parents roles and good care practices of female students of SLTPN 6 Jambi when they are having their periods. There are 532 altogheter 133 (25%) of them are randomly selected as the sample of this research which is conducted from 11-13 of September 2007. Primary data is taken from the sample through questionaire. Univariate analysis reveals that 85% of the respondents have good knowledge; 42,1 of them have good care practices. Furthermore, technique also reveals chi-square is a significant correlation between good knowledge and good care practices with P value = 0,004 (P value < 0,05). The analysis also reveals that parent roles significantly correlate with good care practices with P value = 0,037 (p value = 0,05). From the result of the analysis it can be concludes that some female students of SLTPN 6 Jambi do not take care of themselves when they are having menstruation. So, it is suggested that SLTPN 6 Jambi give more education to its female students about the importance of good care practices during menstruation.